Hybridization despite elaborate courtship behavior and female choice in Neotropical tree frogs - Nali, Renato C. [UNESP]; Zamudio, Kelly R.; Prado, Cynthia P. A. [UNESP] (Wiley, 2022)
The mechanisms of hybridization can be elucidated by analyzing genotypes as well as phenotypes that could act as premating barriers, as the reproductive interactions among heterospecifics can alter the evolutionary history of species. In frogs, hybrids typically occur among species that reproduce explosively (in dense aggregations) with few opportunities for mate selection but are rare in species with elaborate courtship behaviors that may prevent erroneous mating. Using 21 microsatellite markers, we examined hybridization in the prolonged-breeding tree frogs Bokermannohyla ibitiguara and B. sazimai sampled within a contact zone in the Brazilian savanna (72 tadpoles; 74 adults). We also compared acoustic and morphological data. We confirmed both parental species genetically; STRUCTURE results confirmed 14 hybrids, 11 of which were second-generation according to NEWHYBRIDS, all with intermediate values of genetic dissimilarities compared to the parentals. Morphological and acoustic analyses revealed that hybrids showed variable but not necessarily intermediate phenotypes. Moreover, 2 hybrids exhibited call types different from parentals. The reproduction of B. ibitiguara involves territorial and aggressive males, elaborate courtships with acoustic and tactile stimuli, choosy females, and opportunistic strategies. Our study uncovers a rare case of viable hybridization among closely related frogs with such a combination of complex courtship behaviors and mate choice. We discuss the likely directionality and mechanisms behind this phenomenon, and highlight the importance of investigating hybridization even in species that show elaborate reproduction and female choice to advance our understanding of animal diversification.
Keywords: heterospecific mating; hybrid zone; Hylidae; microsatellites; prolonged-breeding